RIGHT HEMIPLEGIA FOLLOWING LIGHTNING STRIKE: CASE REPORT - Aydan Kurtaran; İlker Yıldız and Barın Selçuk and Murat Ersöz and Yasemin Çolak and Müfit Akyüz (Archives of Rheumatology, 2003)
Lightning strike is important because of its high risk of mortality. Although the neurologic changes following lightning have been described frequently, permanent deficit is not frequent. In this case we present a case with right hemiplegia and left corneal perforation after lightning strike. Because of the existing permanent deficits and complications, cases with the same etiology are reviewed.